Limited Access : Transport Metaphors and Realism in the British Novel, 1740-1860 - Takanashi, Kyoko, 1975- (Book collections on Project MUSE., 2022)
"Limited Access employs the trope of reading as travel to consider questions of access, both symbolic and material, in the eighteenth- and nineteenth-century novel. The author draws on media studies and the history of books and examines work by authors including Henry Fielding, Laurence Sterne, Walter Scott, Charles Dickens, William Makepeace Thackeray, and George Eliot"--